Leadership in Education, Corrections and Law Enforcement : a Commitment to Ethics, Equity and Excellence. - Normore, Anthony H. (Advances in Educational Administration, 12., 2011)
This volume fills a unique gap in the knowledge base - the juncture between leadership, ethics, law, and how public institutions/organizations understand and practice the essence of all three. It provides a broad-based view of the intersection where law and ethics meet leadership in multiple professions.